2016
DOI: 10.1007/s11481-016-9705-6
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Meningitis in Patients using Immunosuppressive Medication: a Population-based Prospective Nationwide Study

Abstract: We studied occurrence, presentation, disease course, effect of adjunctive dexamethasone, and prognosis of bacterial meningitis in patients using immunosuppressive medication. Patients were selected from our nationwide, prospective cohort on community-acquired bacterial meningitis performed from March 1, 2006 through October 31, 2014. Eighty-seven of 1447 episodes (6 %) of bacterial meningitis occurred in patients using immunosuppressive medication, and consisted of corticosteroids in 82 %. Patients with bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 29 publications
1
20
0
1
Order By: Relevance
“…Unlike most previously reported outbreaks of invasive meningococcal disease that were associated with serotype B [20], we found that all our cases of meningococcal meningitis were sporadic. According to other studies, L. monocytogenes is the third most common causative agent of CABM and is associated with older age and immunodeficiency [15,[21][22][23][24]. In our study, L. monocytogenes meningitis was the third most common etiological factor and 40% of L. monocytogenes meningitis in our study occurred in adults under the age of 50 without specific risk factors.…”
Section: Discussionsupporting
confidence: 61%
“…Unlike most previously reported outbreaks of invasive meningococcal disease that were associated with serotype B [20], we found that all our cases of meningococcal meningitis were sporadic. According to other studies, L. monocytogenes is the third most common causative agent of CABM and is associated with older age and immunodeficiency [15,[21][22][23][24]. In our study, L. monocytogenes meningitis was the third most common etiological factor and 40% of L. monocytogenes meningitis in our study occurred in adults under the age of 50 without specific risk factors.…”
Section: Discussionsupporting
confidence: 61%
“…L. monocytogenes is an intra-cellular pathogen that is transmitted through contaminated food ( 10 ). It primarily affects elderly or immunocompromised patients, such as cancer patients or those using immunosuppressive drugs ( 8 , 11 , 12 ). Diagnosis of L. monocytogenes meningitis can be challenging due to slow onset of symptoms ( 7 ), atypical cerebrospinal fluid (CSF) findings ( 13 ) consistent with a relatively low grade of infection and high percentage of negative CSF culture ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…In bacterial meningitis, the CSF leukocyte count may exceed 1,000 mm 3 . 5 Patients who are on immunomodulating therapy 13 or are septic 14 or neutropenic 15 often have lower CSF leukocyte counts, or in the case of neutropenia, may have a normal CSF leukocyte count.…”
Section: Serum Biomarkers May Assist In the Diagnosis Of Bacterialmentioning
confidence: 99%